Pemanfaatan Media YouTube sebagai Stimulus Perkembangan Bahasa Anak Usia Dini di Era Digital - Imawati Imawati; Itsnaini Muslimati Alwi (Program Studi Pendidikan Guru PAUD FKIP Universitas Mulawarman, 2026)
The development of digital technology has made YouTube one of the media platforms closely integrated into the lives of young children. This study aims to describe the use of YouTube as a stimulus for early childhood language development and to examine the roles of teachers and parents in supporting this process. The study employed a descriptive qualitative approach at Tiara Tama Posyandu Center, Pacitan, involving 12 children, 2 teachers, and 10 parents as research participants. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using the Miles and Huberman interactive model. The findings indicate that YouTube can stimulate children's language development through vocabulary enrichment, listening skills, speech imitation, speaking ability, receptive and expressive language development, and increased confidence in language use. Children became more active and enthusiastic when learning through educational videos containing songs, stories, and simple vocabulary introductions. An important finding of this study is that the effectiveness of YouTube is determined not only by the quality of its content but also by the active involvement of teachers and parents through questioning, dialogue, and vocabulary reinforcement activities. Therefore, YouTube functions as an effective language stimulus when integrated with social interaction and appropriate adult guidance.